2014
DOI: 10.1177/1090820x13520320
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Selective Cryolipolysis and Reperfusion Recovery for Localized Natural Fat Reduction and Contouring

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 39 publications
2
94
0
5
Order By: Relevance
“…We identified 31 studies (27 prospective clinical studies and four retrospective chart reviews) with a total of 2937 patients that had been treated with LLLT ( n = 1114), cryolipolysis ( n = 706), HIFU ( n = 843) or RF ( n = 116) or other techniques ( n = 158) for subcutaneous fat reduction or body contouring. All studies are summarized by type of device in Tables . All results reported were statistically significant mean changes from baseline measurements unless otherwise noted.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 31 studies (27 prospective clinical studies and four retrospective chart reviews) with a total of 2937 patients that had been treated with LLLT ( n = 1114), cryolipolysis ( n = 706), HIFU ( n = 843) or RF ( n = 116) or other techniques ( n = 158) for subcutaneous fat reduction or body contouring. All studies are summarized by type of device in Tables . All results reported were statistically significant mean changes from baseline measurements unless otherwise noted.…”
Section: Resultsmentioning
confidence: 99%
“…(2014), um grupo tratado com criolipólise em sessões de 60 minutos, nas regiões de abdômen, flancos, culotes, pregas das costas e interno das coxas, obteve redução da adipometria com média de 21,5%, e redução de 19,6% de gordura, resultado observado por meio de exame de ultrassom. Os autores relataram ainda que a redução no tecido adiposo ocorreu de maneira efetiva em até seis meses após o tratamento, não tendo sido observado qualquer efeito colateral, de forma que os pacientes puderam retornar normalmente às suas atividades diárias imediatamente após a aplicação (39).…”
Section: Um Estudo Realizado Por Azevedo E Cols (2008)unclassified
“…Only one treatment was usually necessary but diminishing returns with additional treatments were reported 18 and onset took about 8 weeks 11,44 . In addition to the abdomen 10,18,[45][46] , flank 10-11, 18, 44-48 , buttocks 45 and back 10,[45][46] , specific applicators exist for the arms 50 , knees 10,45 and thighs 10,[45][46][49][50][51][52] . Despite these adaptations, reported results on the trunk tended to exceed those of the extremities 10,45 ( Figures 7, 8, 9).…”
Section: Cryomentioning
confidence: 99%
“…Cryo did not report results using girth as a metric but reported 19.6-25.5% decreased abdominal/flank fat thickness when measured by ultrasound [10][11] . One RF study reported 29% decreased abdominal/flank fat thickness by ultrasound 8 .…”
mentioning
confidence: 99%